PENGEMBANGAN BAHAN AJAR BERBASIS E-BOOK KERAGAMAN RUMAH ADAT DI INDONESIA PEMBELAJARAN IPS KELAS IV SD - Ela Nurjamilah; Tin Rustini; Yusuf Tri Herlambang (Universitas Tanjungpura, 2022)
This research is based on a preliminary study of the 2013 curriculum thematic book which briefly describes the Diversity of Traditional Houses in Indonesia in tabular form. This design and development research has the following objectives: 1) Designing e-book-based teaching materials on the diversity of traditional houses in Indonesia; 2) Testing the feasibility of e-book-based teaching materials on the diversity of traditional houses in Indonesia; and 3) Knowing the responses of teachers and students to e-book-based teaching materials on the diversity of traditional houses in Indonesia. The research method used in this study is the ADDIE model. The ADDIE model has five stages, including analysis, design, development, implementation, and evaluation. This research produces e-book-based teaching materials in the form of applications. The results of the product validation assessment scores from the experts are: 1) material experts show a percentage of 95%; 2) media experts showed very decent results with a percentage of 100%; and 3) linguists show a percentage of 95%. Furthermore, the percentage of the teacher's response is 100% and the percentage of students is 93.3%; on e-book-based teaching materials showed very decent results. From these results, it can be said that the e-book-based teaching materials